Design of a multi-domain information fusion system for urban warfare based on unmanned aerial vehicles - CHEN Lingzi, LI Fei, HAN Shunli (Zhihui kongzhi yu fangzhen)
Urban warfare has become an important form of warfare that cannot be avoided in modern war, and the battle space has changed to multi-domain warfare, cross-domain warfare and all-domain warfare. In order to fully obtain multi-domain and multi-dimensional information of urban environment, effectively support urban combat decision-making and multi-arms coordinated command, a multi-domain information fusion technology system of UAVs for urban combat is proposed. The key technologies of UAV cluster collaborative deployment and networking, autonomous collection of complex urban environmental data, information fusion and spectrum completion across physical space and electromagnetic space, and multi-domain joint spectrum situation evolution prediction are analyzed. It can provide integrated "physical space+electromagnetic space" intelligent visual services for urban combat, urban spectrum intelligent management, and urban wide-area electromagnetic situation assessment and decision-making, effectively enhance the intelligent level of cross-domain information fusion representation in complex urban environments, and provide technical support for urban military and civilian electromagnetic situation intelligent monitoring, electromagnetic space cognition and control.